2020
DOI: 10.3390/app10186477
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) Sorption from Aqueous Solution: A Review

Abstract: Hexavalent chromium (Cr(VI)) in water systems is a major hazard for living organisms, including humans. The most popular technology currently used to remove Cr(VI) from polluted water is sorption for its effectiveness, ease of use, low cost and environmental friendliness. The electrostatic interactions between chromium species and the sorbent matrix are the main determinants of Cr(VI) sorption. The pH plays a central role in the process by affecting chromium speciation and the net charge on sorbent surface. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 95 publications
0
27
0
5
Order By: Relevance
“…This was due to the formation of hydrogen bonds between the groups in C-4-APD or C-2-APZ, which occupy the adsorption sites and make the actual maximum adsorption capacity lower than the calculated value. Furthermore, the large size of Cr2O7 2makes it difficult to enter the adsorption sites, thus limiting the adsorption capacity of Cr2O7 2-(Fenti et al 2020). These results demonstrate that the adsorption of Cr(VI) ions by C-4-APD and C-2-APZ was the monolayer adsorption process.…”
mentioning
confidence: 80%
“…This was due to the formation of hydrogen bonds between the groups in C-4-APD or C-2-APZ, which occupy the adsorption sites and make the actual maximum adsorption capacity lower than the calculated value. Furthermore, the large size of Cr2O7 2makes it difficult to enter the adsorption sites, thus limiting the adsorption capacity of Cr2O7 2-(Fenti et al 2020). These results demonstrate that the adsorption of Cr(VI) ions by C-4-APD and C-2-APZ was the monolayer adsorption process.…”
mentioning
confidence: 80%
“…Due to the negative net charge of Cr 6+ oxyanions, Cr 6+ adsorption is expected to involved electrostatic attraction or anion exchange with positively charged adsorbents sites. The uptake of Cr 6+ should be favored by a pH below the point of zero charge, which would impart the adsorbent a net positive charge (Fenti et al 2020).…”
Section: Adsorption Mechanisms Of Cr 6+ On Different Adsorbentsmentioning
confidence: 99%
“…It has been shown that the reduction reaction (conversion of Cr 6+ to Cr 3+ ) and electrostatic attraction are the main mechanisms of Cr 6+ adsorption on biochar and the reduction reaction had a higher contribution rate than the electrostatic attraction (Guo et al 2020). After conversion of Cr 6+ to Cr 3+ , the resulting Cr 3+ cations may be retained on the adsorbent sites by several mechanisms such as cation exchange, covalent binding, surface precipitation, and coprecipitation of Fe 3+ / Cr 3+ hydroxides (Fenti et al 2020).…”
Section: Adsorption Mechanisms Of Cr 6+ On Different Adsorbentsmentioning
confidence: 99%
“…Among the wide variety of pollutants, hexavalent chromium is by far one of the most toxic pollutants, representing the main threat to living organisms, including humans (Rowbotham et al, 2000). The most widely used strategy for the removal of Cr(VI) from polluted waters and wastewaters is sorption, because of its effectiveness, ease of use, low cost, and environmental sustainability (Fenti et al, 2020). In recent years, biochar has shown interesting properties mitigating the accumulation of hexavalent chromium (Xiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%